ANALISIS PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM BUMN SEKTOR PERTAMBANGAN PERIODE 2007-2010 - Thrisye, Risca Yuliana; Simu, Nicodemus (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 8 No 2 (2013), 2013)
ABSTRACT This research aimed to determine the impact of financial ratios to stock return. The object of this research was state-owned mining companies listed on Indonesia Stock Exchange during 2007-2010 periods. Financial ratios used in this study as the independent variables were current ratio (CR), total assets turnover ratio (TATO), debt-to-equity ratio (DER), and return on assets (ROA). The data used in this research were quarterly data, based on quarterly financial statements, starting from the first quarter of 2007 to the fourth quarter of 2010, which were analyzed using multiple regression analysis. Furthermore, hypothesis was tested using  t-test and F-test based on the 5 percent significance level. Hypothesis tested using t-test showed that the ratio of CR, TATO, and ROA, partially, did not have a positive and significant effect on stock returns. Instead, DER had a negative and significant impact on stock returns. The test results with F-test found that all selected financial ratios did not have significant effect on stock returns. Keywords: CR,  DER, ROA, return, TATO